EKSPRESI IDENTITAS KEACEHAN DALAM INTERAKSI SOSIAL DI TENGAH LINGKUNGAN NON-SYARIAT ISLAM (Studi Kasus pada Komunitas Ikatan Pelajar Aceh Semarang) - -, Buwaizhi - (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2017)
Student Association Aceh Semarang (IPAS) one of a local youth organization of government of Aceh Province located in Central Java, especially the city of Semarang. IPAS community as a place for students Aceh Semarang to express Acehnese in the Non-Shari'a. This study uses the Identity Theory Anthony Giddens. The results of this study indicate that: (1) The identity attached to IPAS community members as a result of identity construction from the region of origin, every individual has a sense of perspective or different about the identity. IPAS community members individually adjust to the new environment. The new neighborhood would be a challenge for any community member IPAs to make adjustments. (2) Community IPAS did some ways to express Acehnese in the Non-Shari'a, such as through social, cultural religious funds. (3) There are three factors that affect the community IPAS in mengepresikan Acehnese in the Non-Islamic Shari'ah, namely minorities, cultural differences and social environment. It is these factors that trigger IPAS community to show the Acehnese in a new environment.Keywords: Acehnese identity , Aceh Student Association Semarang ( IPAS ) , Environmental Non - Shari'a .